Tunability Dependence of All-Optical Liquid Crystal Delay Line on Laser Polarization and Incidence Angle - Li, Jinfeng (Photonics Letters of Poland, 2023)
This work experimentally investigates the optical manipulation of trans-cis swaps and resultantly their optical/electromagnetic imprints as a driver for realizing the tunable delay lines in the microwave X band (8-12 GHz) regime utilizing the polarization and incident angle dependencies of azo-admixed liquid crystals (LCs). Measurement results confirm that the tuning efficacy of the azo-LCs-based delay line is highly dependent on the polarization of the laser beam concerning the rubbing and filling directions of LCs. When the laser light beam is polarized parallel to the rubbed direction as well as the LCs filling direction, the achievable differential phase shift is maximized. Full Text: PDF References T. Sakamoto, Optoelectronic Circuits for Control of Lightwaves and Microwaves (London, IntechOpen 2011). CrossRef J.F. Li, "All-optically controlled microwave analog phase shifter with insertion losses balancing", Eng. Lett. 28, 3 (2020). DirectLink J.P.F. Lagerwall, G. Scalia, "A new era for liquid crystal research: Applications of liquid crystals in soft matter nano-, bio- and microtechnology", Curr. Appl. Phys. 12, 6 (2012). CrossRef S. Kim, K. Seiji, "Photochemical On–Off Switching of One-Dimensional Photonic Crystals Consisting of Azo-Functionalized Liquid Crystal Polymer and Polyvinyl Alcohol", Crystals 9, 12 (2019). CrossRef J.F. Li, "Micro-LED Mass Transfer Technologies", ICEPT (Guangzhou, IEEE 2020). CrossRef U. Chodorow, J. Parka, O. Chojnowska, "Liquid Crystal Materials in THz Technologies", Phot. Lett. Poland 4, 3 (2012). CrossRef